Perbedaan Kadar Low Density Lipoprotein Antara Penderita Ulkus Diabetik dan Tanpa Ulkus Diabetik pada Pasien Diabetes Melitus Tipe 2 di RSUD Dr. Moewardi - Putri, Hardistya Rizki Novella; , dr. Nur Hidayat, Sp. PD; , dr. Iin Novita Nurhidayati Mahmuda, M.Sc., Sp.PD (2015)
Background. The incidence of Diabetes Mellitus has increased every year that was followed by increasing one of the complications of diabetic ulcers. Diabetic ulcers caused by several risk factors one of them is increased levels of Low Density Lipoprotein (LDL). These risk factors can lead to atherosclerosis which leads to an increased incidence of diabetic ulcers. Objective. Knowing the differences in LDL cholesterol among patients with diabetic ulcers and without diabetic ulcers in patients Diabetes MellitusType 2. Methods. This study was an observational study with cross sectional approach. Taken 27 diabetic type 2 patients with diabetic ulcers and 27 patients without diabetic ulcers. The technique waspurposive sampling with a sample of Type 2 DM patients with diabetic ulcers andwithout diabetic ulcers outpatient and inpatient care in Dr. Moewardi hospitals. The statistical test used t test - unpaired. Results. The average result of the difference in LDL cholesterol among Type 2 DM patients with diabetic ulcers and withoutdiabetic ulcers is 107.93 and 104.22. The researchers can deduce the average of LDL cholesterol Type 2 DM patients with diabetic ulcers was higher than without diabetic ulcers. P value (sig) amounted to 0,006 so that this study found a significant difference. Conclusion. Based on the results of the research, concluded there is a difference in LDL cholesterol among patients with diabetic ulcers andwithout diabetic ulcers in patients Type 2 Diabetes Mellitus in Dr. MoewardiHospital, with the average of LDL levels in Type 2 diabetic patients with diabetic ulcers was higher than without diabetic ulcers.